Impaired border zone formation and adverse remodeling after reperfused myocardial infarction in cannabinoid CB2 receptor deficient mice - Duerr, Georg D.; Heinemann, Jan C.; Gestrich, Christopher; Heuft, Tobias; Klaas, Timo; Keppel, Katharina; Roell, Wilhelm; Klein, Alexandra; Zimmer, Andreas; Velten, Markus; Kilic, Ana; Bindila, Laura; et al. (Life Sciences, 2015)
Aims: Reperfusion ofmyocardial infarction is associated with inflammatory reaction and subsequentmyocardial remodeling with a rapid scar formation in mice. The cannabinoid receptor CB2 has been associated with cardioprotection and regulation ofmacrophage function.Weinvestigated its role in remodeling of reperfused infarction. Main methods: One hour LAD-occlusion was followed by reperfusion over 6 h and 1, 3 and 7 days in wild-type C57/BL6J (WT) and CB2 receptor-deficient (Cnr2-)mice (n=8/group). Hearts were processed for functional, morphological and mRNA/protein analysis, and tissue concentration of endocannabinoidswas determined using liquid chromatography-multiple reaction monitoring. Key findings: In contrast to a rapid formation of granulation tissue and a compacted non-transmural scar inWT mice after 7 days of reperfusion, Cnr2-/- mice showed a non-compacted transmural scar. Millar left ventricular catheter measurements revealed a significantly worse function in Cnr2- mice.We found no compensatory elevation of endocannabinoid concentration in Cnr2-/- hearts. Macrophage infiltration was significantly stronger in Cnr2- hearts and affected also the remote septum, when compared to WT hearts.We found a cytokine-driven inflammatory response in Cnr2- hearts with no significant induction of chemokines. Immunohistochemistry for thrombospondin-1 revealed a dysfunctional infarction border zone formation in Cnr2- hearts. Cnr2- hearts showed no significant induction of tenascin C, collagen-Ia or lysil oxidase, thereby indicating adversemyocardial remodeling. Significance: Endocannabinoids act via CB2 receptor in the modulation of inflammatory response and myocardial remodeling after infarction. CB2 receptor plays an important role in the formation of infarction border zone, collagen deposition and organization of stable scar during remodeling.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Endocannabinoids; Infarction border zone; Ischemia; Reperfusion; Thrombospondin